Structure, principle, and application of magnetic field-assisted pulsed laser deposition: An overview. (May 2023) - Lu, Yimin; Yang, Chunlai; Wang, Hai; Ma, Lifang; Xu, Manman; Xi, Lin
Abstract: One of the most significant developments in pulsed laser deposition (PLD) technology is the introduction of external magnetic fields to affect the generation, expansion, diffusion, and nucleation of particles during deposition, which is completely different from its counterpart in magnetron sputtering (MS) and filtered vacuum cathode arc (FVCA). This overview summarizes the various structures and principles of the magnetic field introduced in PLDs. The effects of the magnetic field on the various properties of the PLD-grown nanomaterials were reviewed, and the reasons or probable causes were analyzed. These grown materials were applied in the different fields due to their novel optical, magnetic, and mechanical properties, which was overviewed emphatically in this manuscript. This overview intends to assist researchers working on PLD-grown materials. Highlights: Novel process of magnetic field-assisted PLD was paid attention. Different nanomaterials grown by magnetic field-assisted PLD was overviewed. Various structures of the magnetic field-assisted PLD were shown. Outlook on development of magnetic field-assisted PLD was carried out.